The Treatment of Iron Making Blast Furnace Dust by Chloride Hydrometallurgy - G. Van Weert; S. Honingh; R. E. Johnson; W. Kat; B. R. Palmer; van Sandwijk A. (Society for Mining, Metallurgy & Exploration, 1993)
In-plant recycling of dust from iron making BF's creates undesirable circulating loads of volatile trace elements such as zinc and lead. Disposal of such dusts creates environmental problems, hence a separate treatment is indicated. Since the bulk of the zinc and lead compounds occurs in the fine dust fraction; hydrocycloning the slurry from the BF gas cleaning operation results in upgrading the material for treatment. A process has been proposed, whereby the zinc and lead are solubilized from the fine fraction with spent hydrochloric acid from steel pickling. The stoichiometry of this autoclave oxidation process is adjusted to simultaneously precipitate, by oxyhydrolysis, most of the iron for recycling to the BF's. Lead and zinc are successively recovered from the filtrate as low chloride precipitates. This paper describes additional testwork, leading to the design of a pilot plant which was planned to begin operation in 1992.